The effect of fiber orientation on the post-cracking behavior of steel fiber reinforced concrete under bending and uniaxial tensile tests. (October 2018) - Mudadu, Antonio; Tiberti, Giuseppe; Germano, Federica; Plizzari, Giovanni A.; Morbi, Alessandro
Abstract: The present paper deals with an experimental study on the post-cracking tensile behavior of Steel Fiber Reinforced Concrete (SFRC). In this regard, a broad experimental campaign based on Uniaxial Tensile Tests (UTTs) on notched cylinders as well as three point bending tests (3 PBTs) on notched beams was carried out. Based on the experimental results, the benefits offered by the addition of fiber in the post-cracking behavior was deeply studied: fibers increase the toughness of concrete and the ultimate crack width. The uniaxial post-cracking tensile laws of SFRCs were directly obtained by UTTs and indirectly retrieved by 3 PBTs by performing an inverse analysis procedure. In the latter case the fracture energy was generally higher. It was proven that there is a strongly dependency of the SFRC post-cracking performance with the fiber distribution and orientation that was measured by means of image-analysis technique.